Real-time Study for Uses of Opened Multidose Vials of Live Attenuated Bivalent Oral Polio Vaccine: Real-time Study for Uses of Opened Multidose Vials of Live Attenuated Bivalent Oral Polio Vaccine - Kumar, Dr. Amit (International Journal of Pharmaceutical & Biological Archive, 2020)
Introduction: This study was aimed to find out real-time for the use of opened multidose vials of live attenuated bivalent oral polio vaccine (bOPV) containing type I and III. Materials and Methods: The study was performed in continuation of a preliminary study with opened multidose bOPV vials of only five batches and established use of the safe and efficacious form of the vaccine up to 56th day (8 weeks) after opening and then stored at +4°C temperature. In the current study, collected samples from ten bOPV batches were divided into two types; one type samples were stored at +4°C temperature and second type samples were stored at −20°C temperature and both types samples were studied in the real-time study for safe and efficacious use of the opened multidose vials in subsequent immunization sessions on weekly intervals from 1st week to 8th week. A total of six critical and quality attributes of the vaccine were studied, that is, potency, identity, sterility, pH, kanamycin activity, and vaccine vial monitor (VVM) status. After completion of the 8th week, the study was performed to find out the real-time and temperature for the uses of the vaccine, and all quality attributes were performed on a daily basis to the withdrawal of the subsequent sessions. Results and Discussion: Results of all the quality attributes (potency, identity, sterility, pH, kanamycin activity, and VVM status) were qualified the acceptance criteria as mentioned in Indian Pharmacopeia-2018 and obtained results of one type samples (stored at +4°C temperature) were compared with the same batches second type samples; stored at −20°C temperature use as a reference standard. The real-time study suggested that opened multidose live attenuated bOPV vials can use in safe and efficacious conditions up to 59th day after opening and stored at +4°C temperature. Conclusion: This study provides scientific strength to decide the real-time uses of efficacious and safe conditions of opened multidose live attenuated bOPV vials after withdrawal subsequent sessions only up to 59th day after opening and stored at +4°C temperature.